Feasibility of convalescent plasma therapy in severe COVID‐19 patients with persistent SARS‐CoV‐2 viremia. Issue 9 (3rd May 2021) - Camou, Fabrice; Tinevez, Claire; Beguet‐Yachine, Mathilde; Bellecave, Pantxika; Ratiarison, Diana; Tumiotto, Camille; Lafarge, Xavier; Guisset, Olivier; Mourissoux, Gaëlle; Lafon, Marie‐Edith; Bonnet, Fabrice; Issa, Nahéma
Abstract: This study aims to assess the efficacy and safety of convalescent plasma therapy (CPT) in COVID‐19 critically ill patients with protracted severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) RNAemia. A retrospective cohort study was conducted in intensive care unit (ICU). All patients with severe COVID‐19 pneumonia for whom RNAemia remained positive more than 14 days after onset of the infection were included and given CPT. The primary objective was to evaluate SARS‐CoV‐2 RNAemia 7 days (D7) after CPT. A total of 14 patients were included and they received a median CPT volume of 828 ml (range: 817–960). CPT was administered in a median time of 14 days after ICU admission. At D7, 13/14 patients had negative SARS‐CoV‐2 blood PCR and one patient had negative blood PCR 11 days after CPT. At D7 and at D14, the clinical status was improved in 7/14 and 11/14 patients, respectively. The 28‐day mortality rate was 14%. No CPT‐related adverse effects had been reported. CPT is safe and may be efficient in patients with protracted RNAemia admitted in ICU for severe COVID‐19 pneumonia. Randomized controlled trials are needed to confirm these results.